DUPE: Duplicated Unicast Packet Encapsulation in Position-based Routing VANET - Ye Tao; Xin Li; Tsukada, Manabu; Esaki, Hiroshi (2016 9th IFIP Wireless and Mobile Networking Conference (WMNC), 2016)
Position-based Routing Vehicular Ad-hoc Network (PBR-VANET) is a specific type of mobile Ad-hoc network where the nodes are present as vehicles and the routing is decided based on node position. However, PBR-VANET routing protocols greatly suffer from mass packet loss due to frequent changes in topology. We discuss the requirements of the routing protocol and propose a routing encapsulation protocol called Duplicated Unicast Packet Encapsulation (DUPE). The protocol is compatible with original GeoNetworking standard, and can cooperate with the existing implementations without modification to neither GeoNetworking infrastructure nor user applications. The protocol encapsulates GeoNetworking packet in BTP packet (a Layer 4 protocol in GeoNetworking) and duplicates the original packet into different paths to reduce packet loss caused by failure and stale paths. The evaluations on DUPE in different scenarios show that, with reasonable latency and bandwidth overhead achieved, packet loss in certain scenarios is eliminated, where standard GeoNetworking protocol has packet loss of up to 94.5% in worst case.